1981
DOI: 10.1017/s0022029900021543
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between triglyceride structure and softening point of milk fat

Abstract: Eight samples of milk fat were selected for softening point (SP) range. They were separated into high, medium and low molecular weight triglyceride fractions by silicic acid-column chromatography to enable further separation into triglyceride classes by silver ion adsorption thin-layer chromatography. Correlation between triglyceride class content and SP was low. The molecular species composition of the triglyceride classes was determined and correlated with SP. The best correlations were between SP and some l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…as outlined by Parodi (1970Parodi ( , 1972 and cis-and trans-monoenoic acids were separated by t.l.c. as reported by Parodi (1981).…”
Section: Fatty Acid Analysissupporting
confidence: 72%
See 2 more Smart Citations
“…as outlined by Parodi (1970Parodi ( , 1972 and cis-and trans-monoenoic acids were separated by t.l.c. as reported by Parodi (1981).…”
Section: Fatty Acid Analysissupporting
confidence: 72%
“…The positional distribution of the fatty acids in the triglyceride classes from the high, medium and low molecular weight fractions are presented in Tables 2, 3 and 4 respectively. The 5 triglyceride classes SSS, SSM', SSM C , SM C M< and SM C M C represent approximately 90 % of the triglycerides of milk fat (Parodi, 1981). The class designated 'other' contains small amounts of triglycerides such as SSD, MMM, SMD, MMD, SDD, SST etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using inteeresterification to modify the physical properties of butter is not a recent idea (1)(2)(3)(4). deMan et aL (5) and Antila (6) reported that inteeresterification of milkfat markedly increases its hardness, affects the melting properties and changes the peak ratios in melting curves.…”
Section: Abstract: Butter Oil High-melting Glyceride Interesterifimentioning
confidence: 99%
“…It begins around 21 °C and continues until the final melting of milk TAG below 39 °C. Milk fat has lower melting temperature than would be expected from its fatty acid (FA) composition, which is a result of the non-random esterification of FA in TAG reflecting the complex regulation of de novo FA synthesis, desaturation and uptake of long chain FA, and further TAG synthesis, in mammary gland (Leskinen et al, 2016;Leskinen et al, 2019;Leskinen, Ventto, Kairenius, Shingfield, & Vilkki, 2019;Parodi, 1981Parodi, , 2004Timmen & Patton, 1989;Tzompa-Sosa, van Valenberg, van Aken, & Bovenhuis, 2016).…”
Section: Introductionmentioning
confidence: 99%